2012
DOI: 10.1371/journal.pone.0029908
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Epidemiologic, Histopathologic and Molecular Features of an Unexplained Dermopathy

Abstract: BackgroundMorgellons is a poorly characterized constellation of symptoms, with the primary manifestations involving the skin. We conducted an investigation of this unexplained dermopathy to characterize the clinical and epidemiologic features and explore potential etiologies.MethodsA descriptive study was conducted among persons at least 13 years of age and enrolled in Kaiser Permanente Northern California (KPNC) during 2006–2008. A case was defined as the self-reported emergence of fibers or materials from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 21 publications
3
107
0
2
Order By: Relevance
“…Tipik olarak hastalar, derideki varsandıkları patojeni ortadan kaldırmak için kendilerine zarar verecek şekilde tırnak, cilt soyucu, cımbız gibi gereçlerle ciltte yara, erozyonlara yol açabilirler. [9][10][11][12] Hastamız böceklerle vücudunun istila olduğunu düşünen klasik bir olguydu; görsel varsanısı nedeniyle evinde pestisit kullanmıştı ve kaşıma, tırnakları ile kazı-ma yoluyla cildinde yaralara neden olmuştu.…”
Section: Discussionunclassified
“…Tipik olarak hastalar, derideki varsandıkları patojeni ortadan kaldırmak için kendilerine zarar verecek şekilde tırnak, cilt soyucu, cımbız gibi gereçlerle ciltte yara, erozyonlara yol açabilirler. [9][10][11][12] Hastamız böceklerle vücudunun istila olduğunu düşünen klasik bir olguydu; görsel varsanısı nedeniyle evinde pestisit kullanmıştı ve kaşıma, tırnakları ile kazı-ma yoluyla cildinde yaralara neden olmuştu.…”
Section: Discussionunclassified
“…Note that the single fiber strands on the side of the twisted cotton thread are closer in size to that of the MD fiber depicted here. The fact that the CDC study only used a dermoscope in the search for filaments may explain why only cotton fibers were found in that study, and so the opportunity to find the smaller filaments found in MD was missed 9 .…”
Section: Clinical Features-dermatologicalmentioning
confidence: 97%
“…In 2012 Pearson et al published a long awaited Centre of Disease Control (CDC) sponsored study on the possible causes of MD 9 . The key findings of this study of only 115 patients were: median age 52, 77% female, 77% Caucasian, 70% chronic fatigue symptoms, 54% reported poor state of health, 59% were found to have cognitive defects on testing, 63% had somatic complaints, 50% had detectable drugs in hair analysis and 78% reported exposure to solvents.…”
Section: Historical Matters From An Organic Viewpointmentioning
confidence: 99%
“…This condition, also called Morgellon's disease, has defied easy identification of the causative organisms. Even the Center for Disease Control's efforts to identify the cause have not yet found the specific infectious agent or agents that cause this debilitating condition (1).…”
Section: Advances In and Hope For The Treatment Of Parasitosismentioning
confidence: 99%